A ESCOLA, A FAMÍLIA E O ESTADO: UMA APROXIMAÇÃO HISTÓRICA DE SUAS RELAÇÕES - Pierre Caspard; Tradução: Maria Helena Camara Bastos (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2011)
The historiography of education focused, particularly in France, the role of two successive major institutional players: the church and state. This article draws attention to the work of families, the sixteenth to the nineteenth century, the different levels of education: primary, secondary, technical. It concludes with the need to exploit the available sources to reassess this action to give its proper place in the socio-cultural dimension of the history of education, and also to better understand why some major problems today by the French educational system.